Pembelajaran PEMBELAJARAN SENI TARI DALAM PROGRAM KHUSUS SENI BUDAYA (KKSB) DI SMP PGRI 1 BUDURAN SIDOARJO - Aisyah Rachma Febrianti Putri; Bambang Sugito (Universitas Negeri Surabaya, 2026)
: Dance learning plays an important role in developing students' creativity, character, and cultural appreciation. One form of dance learning implementation in schools is through the Special Arts and Culture Class Program (KKSB). This study aims to describe the planning and implementation of dance learning in the Special Arts and Culture Class Program (KKSB) at SMP PGRI 1 Buduran Sidoarjo. The study used a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation. Research informants consisted of the vice principal, arts and culture teachers, dance trainers, and KKSB students. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that dance learning planning in KKSB includes determining learning objectives, compiling traditional and creative dance materials, selecting demonstration and practice methods, and using learning media in the form of accompanying music and dance videos. The learning implementation was carried out through introductory, core, and closing activities with an emphasis on direct practice, movement exploration, routine practice, and dance performance. The KKSB program has been proven to improve students' dance skills, creativity, discipline, cooperation, and appreciation of local culture. Thus, the KKSB program is an effective means of developing dance skills while supporting local cultural preservation efforts through structured and sustainable learning.